Transformasi Perpustakaan Berbasis Inklusi Sosial sebagai Pusat Kegiatan Masyarakat - Handayani, Fitri; Suriyadi (Perpustakaan Universitas Gadjah Mada, 2025)
In today's era of technological advancement, libraries are no longer merely buildings providing books and services, but also function as facilitators of community empowerment. Libraries have a more complex function in building an empowered community. The social inclusion-based library transformation program is a strategic effort to expand the library's function as a learning center, a center for community activities, and a means of socio-economic development. This study aims to describe the social inclusion-based library transformation program as a center for community activities at the Sungai Penuh City Library and Archives Office. The study used a qualitative approach with a case study method. Data were collected through semi-structured interviews and documentation, then analyzed using thematic analysis. The results show that libraries have played a role as an information center, an educational recreation center, a center for cultural preservation, a center for community empowerment, and a center for improving the quality of human resources. These findings indicate that libraries are capable of becoming hubs for community social activities and contributing to increased welfare. Future research is recommended to examine the creative economy and the inclusiveness of library services in more depth. Keywords: library; transformation; social inclusion; society